Perfil dietético de mulheres com disfunção temporomandibular dolorosa muscular crônica: um estudo observacional - Nogueira, Sandra Maria Abreu (2024)
Temporomandibular Disorder (TMD) is the main chronic pain that affects the face, and is associated with dietary changes due to pain and function limitation. However, there is a scarcity of studies on the impact of this disorder on nutrition and vice versa. This study aimed to evaluate and compare the consumption of energy and nutrients among chronic TMD and asymptomatic women, and also to evaluate data according to Dietary Reference Intakes (DRIs) and the World Health Organization (WHO) values. In this analytical cross-sectional study, a sample consisted of 84 women who were evaluated according to the Diagnostic Criteria for TMD (DC/TMD), and then allocated into two groups: asymptomatic group, composed of women without TMD (n=16); and TMD group, composed of women diagnosed with myalgia (DC/TMD) (n=68). In terms of data collection, participants were assessed using three 24-hour food recalls and analyzed in the Nutwin program for the analysis of energy and nutrient content. The Multiple Source Method (MSM) program was used to correct for intra- individual variability and to estimate participants' usual dietary consumption. Energy and nutrients consumption was also analyzed according to the DRI and WHO values as the cutoff point. To characterize the behavioral profile of the participants, the Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HAD), Pain Catastrophizing Scale (B-PCS), Oral Behavior Checklist (OBC-DC), International Physical Activity Questionnaire (IPAQ) and Jaw Functional Limitation Scale (JFLS-20) were used. The obtained data were analyzed using SPSS 25.0 software. The data were considered significant when the p-values were ≤ 5%. The TMD group showed significantly higher PSQI, B-PCS, OBC, JFLS global and JFLS chewing scores. When compared to asymptomatic group, TMD group showed lowered mean intake of cholesterol polyunsaturated fat, sodium, omega-3, omega-6, folate, magnesium, selenium, and increased mean intake of trans fat. The healthy group consumed polyunsaturated fat above the recommended and TMD group showed a higher prevalence of inadequacy of selenium and folate intake. Therefore, nutritional inadequacies were observed in both groups, however TMD group had a significantly lower intake of nutrients previously associated with chronic pain.